OVERVIEW OF FIXED-POINT THEORY AND ITS APPLICATIONS: A REVIEW - Rakhi Namdev, Rashmi Tiwari, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In the present paper, a review on fixed point theory is given. Fixed point theory plays an important role in pure and applied mathematics. The contribution by various authors for said topic is discussed.